A Literature Review on Cybersecurity Risks and Challenges Assessments in Virtual Power Plants: Current Landscape and Future Research Directions - Razan Alajlan; M. M. Hafizur Rahman; Mohammed Al-Naeem; Mohammed Amin Almaiah (IEEE Access)
Virtual Power Plants (VPPs) have emerged as dynamic solutions, harnessing the distributed resources such as solar panel and batteries. However, the complicated interconnectedness of VPPs exposes them to unique cybersecurity vulnerabilities, distinguishing them from traditional smart grids. This systematic literature review primarily focuses on the cybersecurity challenges VPPs face, such as data breaches and data flow manipulation. The study explores these unique risks based on proposed solutions from the existing literature like federated learning, intrusion detection systems, blockchain integration, and machine learning by analyzing their strengths, weaknesses, and applicability to VPP cybersecurity. Additionally, regulatory barriers and opportunities like cost-savings are discussed, with a focus on ensuring the secure future of VPPs through machine and deep learning and strong security policies. This paper contributes significantly to the field by identifying VPP cybersecurity risks, evaluating potential solutions, and proposing future research directions.